Breastfeeding practice during disasters: Challenges and barriers for public health - Inke Malahayati; Safrina; Tengku Sri Wahyuni; Lenny Nainggolan (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Breastfeeding is essential for protecting infant and maternal health and fosters public health benefits, especially in disaster scenarios where health services are compromised. It crucially helps prevent infection, malnutrition, and infant mortality, yet rates remain low among vulnerable populations in emergencies. The aim of this study is to explore the enabling and inhibiting factors influencing breastfeeding practices during disasters while also assessing how structural, socio-economic, and cultural determinants shape these practices. Methods: A systematic literature review was conducted in this study. A systematic search was conducted using Google Scholar, PubMed, and Scopus for full-text articles published between 2019 and 2025. Keywords such as “breastfeeding and mitigation” and “breastfeeding and disasters” were used. We selected ten studies using either qualitative or quantitative methods for analysis after removing duplicate and ineligible articles (including reviews and opinion articles). Findings: Successful breastfeeding during disasters relies on understanding its benefits, community support, adherence to cultural practices, and mental health services for mothers. Barriers include a lack of awareness about breastfeeding support, unclear protocols for formula distribution, economic pressures, disrupted healthcare, and psychological stress. Quantitative studies indicate a decrease in exclusive breastfeeding rates, while qualitative research highlights the importance of coordinated support from multiple stakeholders. Conclusion: To protect and promote breastfeeding during emergencies, it is crucial to establish clear institutional guidelines and regulations on formula donations, enhance mental health support for mothers, and strengthen nutrition education and community outreach. Novelty/Originality of this article: This review uniquely integrates global evidence from 2019 to 2025 across various disaster contexts, offering practical insights for developing an effective and cost-efficient emergency response framework for breastfeeding support.